Targeted mutagenesis of multiple and paralogous genes in Xenopus laevis using two pairs of transcription activator‐like effector nucleases. (11th December 2013) - Sakane, Yuto; Sakuma, Tetsushi; Kashiwagi, Keiko; Kashiwagi, Akihiko; Yamamoto, Takashi; Suzuki, Ken‐ichi T.
<x xml:space="preserve">Abstract</x> Transcription activator‐like effector nucleases (TALENs) have been extensively used in genome editing in various organisms. In some cases, however, it is difficult to efficiently disrupt both paralogous genes using a single pair of TALENs in Xenopus laevis because of its polyploidy. Here, we report targeted mutagenesis of multiple and paralogous genes using two pairs of TALENs in X. laevis. First, we show simultaneous targeted mutagenesis of three genes, tyrosinase paralogues (tyra and tyrb) and enhanced green fluorescent protein (egfp) by injection of two TALENs pairs in transgenic embryos carrying egfp. Consistent with the high frequency of both severe phenotypic traits, albinism and loss of GFP fluorescence, frameshift mutation rates of tyr paralogues and egfp reached 40–80%. Next, we show early introduction of TALEN‐mediated mutagenesis of these target loci during embryogenesis. Finally, we also demonstrate that two different pairs of TALENs can simultaneously introduce mutations to both paralogues encoding histone chaperone with high efficiency. Our results suggest that targeted mutagenesis of multiple genes using TALENs can be applied to analyze the functions of paralogous genes with redundancy in X. laevis.